Assessing (in)equality in the structural covariates of drug-specific arrest counts - Thomas, Shaun A. (Crime & delinquency, 2018)
Prior research assessing the structural covariates of drug arrests has focused on composite measures of arrests. Prior studies have also neglected to simultaneously consider the influence of characteristics of communities, law enforcement agencies, police officers, and drug-specific mortality rates on drug-specific arrests. As such, the extant literature offers an incomplete understanding of the structural correlates of drug arrests. The current study addresses these limitations by assessing the structural covariates of drug-specific measures of arrests for cocaine, crack, heroin, marijuana, and methamphetamine. Results highlight substantive distinctions in the structural covariates of drug-specific arrests across places, particularly related to racial diversity within the community and local police departments, and drug-specific mortality (i.e., overdose) rates findings that have important implications for future research.